Prevalence of intestinal parasitic infections and associated risk factors for hookworm infections among primary schoolchildren in rural areas of Nakhon Si Thammarat, southern Thailand - Chuchard Punsawad; Nonthapan Phasuk; Suchirat Bunratsami; Kanjana Thongtup; Parnpen Viriyavejakul; Sarawoot Palipoch; Phanit Koomhin; Somchok Nongnaul (BMC Public Health, 2018)
Abstract Background Soil-transmitted helminth (STH) infections are among the most common type of infections worldwide and are widely distributed in tropical areas. In rural areas of southern Thailand where most land is used for agriculture, children are at risk of acquiring parasites, especially STHs. Assessing the current situation regarding parasitic infection in these areas is a prerequisite for developing appropriate control measures. This study is aimed at determining the prevalence of intestinal parasitic infections, the intensity of STH infections and the associated risk factors among primary schoolchildren in Nopphitam District, Nakhon Si Thammarat Province, Thailand. Methods A cross-sectional study involving 299 schoolchildren between 7 and 12 years of age was conducted between January and March 2016. A questionnaire administered by direct interviews was used to collect sociodemographic information and data on associated risk factors. Stool samples were processed using direct wet smears, formalin-ethyl acetate sedimentation concentration, and the modified Kato-Katz technique. Results The overall prevalence of intestinal parasites among the 299 children was 16% (48 of 299), with 32 children infected with hookworms (10.7%), 10 with Blastocystis hominis (3.3%), seven with Giardia intestinalis (1.6%), one with Enterobius vermicularis (0.3%), and one with Trichuris trichiura (0.3%). The hookworm infection intensity, measured by the median eggs per gram (EPG) of stool, was 1200 EPG (Interquartile range (IQR): 360–3200). Most children had light-intensity hookworm infections, but two had heavy-intensity infections. When participants included in the sample were classified by age, children 10–12 years old demonstrated higher intestinal parasite prevalence than those aged 7–9 years (adjusted odds ratio (AOR) = 2.3, 95% CI: 1.1–4.9, P = 0.030). Inadequate handwashing before meals was statistically associated with hookworm infections (AOR = 2.3; 95% CI: 1.1–4.8, P = 0.037). Conclusions This study highlights that hookworms are the most prevalent STH infection in the study area. Older age group (10–12 years) and inadequate handwashing before meals were statistically associated with hookworm infections. Accordingly, appropriate strategies and education on personal and environmental hygiene should be implemented. Moreover, the cost-effectiveness of mass drug administration in this area should be further investigated.